Implikasi Laba Operasi dan Modal Kerja terhadap Laba Bersih PT. Nippon Indosari Corpindo - Nurul Auliya; Pra Gemini; Abdullah Abdullah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In the background of this research problem, namely, operating costs have increased and working capital has decreased while net profit has increased, which should make high operating costs lower profits and lower working capital lower net profit. The occurrence of this phenomenon so researchers raised this issue.This study uses quantitative research methods and sampling using purposive sampling techniques with homogeneous sampling category criteria. The results of the research found from the three variables used that have an influence, namely operating profit has a significant effect on net profit with a value of 0.0000 and after being tested simultaneously operating profit also has a significant effect on net profit with a value of 0.0000 while working capital has no effect on net profit with a value of 0.1483. From the results of the study, the authors draw a conclusion that working capital does not always decrease will make net profit decrease. excess income is based on low operating profit and high working capital.